1984
DOI: 10.1159/000233512
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycol Reactive Antibodies in Man: Titer Distribution in Allergic Patients Treated with Monomethoxy Polyethylene Glycol Modified Allergens or Placebo, and in Healthy Blood Donors

Abstract: Antibodies to polyethylene glycol (PEG) were analyzed in patients with various allergies and in healthy blood donors employing passive hemagglutination. In untreated allergic patients and in healthy blood donors, naturally occurring anti-PEG antibody titers between 32 and 512 were seen in 3.3 and 0.2%, respectively. During hyposensitization with monomethoxy polyethylene glycol modified ragweed extract and honey bee venom, respectively, the patients showed an anti-PEG antibody response. Titers of 32–512 were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
161
3
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(170 citation statements)
references
References 5 publications
2
161
3
2
Order By: Relevance
“…Interestingly, there have been several reports on the detection of anti-PEG antibodies in healthy blood donors, who have not received PEGylated biopharmaceuticals, suggesting that environmental PEG exposure may lead to the development of anti-PEG antibodies in a subset of the population (Richter and Akerblom 1984;Garratty 2004Garratty , 2008Armstrong et al 2007;Garay et al 2012). Moreover, PEG is used during manufacturing of certain vaccines and plasma-derived biopharmaceuticals, for example, certain influenza virus vaccines (Polson 1976), hepatitis B virus vaccines (Takao et al 1986), and plasma-derived FVIII products (Chtourou 2012).…”
Section: Immunogenicity Of Pegmentioning
confidence: 99%
“…Interestingly, there have been several reports on the detection of anti-PEG antibodies in healthy blood donors, who have not received PEGylated biopharmaceuticals, suggesting that environmental PEG exposure may lead to the development of anti-PEG antibodies in a subset of the population (Richter and Akerblom 1984;Garratty 2004Garratty , 2008Armstrong et al 2007;Garay et al 2012). Moreover, PEG is used during manufacturing of certain vaccines and plasma-derived biopharmaceuticals, for example, certain influenza virus vaccines (Polson 1976), hepatitis B virus vaccines (Takao et al 1986), and plasma-derived FVIII products (Chtourou 2012).…”
Section: Immunogenicity Of Pegmentioning
confidence: 99%
“…It appears that the haptogenic character of PEG depends on its structure and molecular weight, immunogenicity of the anchoring protein, and the presence of adjuvant. 9,15,17) Several reports have demonstrated that PEGylated protein products elicit anti-PEG antibodies (mainly anti-PEG IgM) in animals and humans.…”
Section: Anti-peg Immunoglobulin M (Igm) Response To Pegylated Proteinsmentioning
confidence: 99%
“…In addition, surprisingly, in healthy blood donors with no known prior exposure to PEG, the prevalence of anti-PEG antibodies has been detected up to 25%, 8) which contrasts with a 0.2% occurrence reported over 20 years ago. 9) This increase may be due to greater exposure to PEG in cosmetics, pharmaceuticals and processed foods. There is concern that anti-PEG antibodies limit the efficacy of PEGylated substances because they lead to enhanced blood clearance of PEGylated substances and decreased biological activity of the substances by neutralization.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, mPEG-RBCs (syngeneic, allogeneic and xenogeneic) show decreased immunogenicity. A number of studies show that, while PEG has low immunogenic potential, it does (under some circumstances) induce anti-PEG antibodies [32][33][34][35]. Typically, in animal models this has required the co-administration of Freund's Complete Adjuvant or coupling of PEG to highly immunogenic proteins [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies show that, while PEG has low immunogenic potential, it does (under some circumstances) induce anti-PEG antibodies [32][33][34][35]. Typically, in animal models this has required the co-administration of Freund's Complete Adjuvant or coupling of PEG to highly immunogenic proteins [32,33]. More recently, studies have reported that a significant percentage of normal blood donors show evidence of anti-PEG antibodies [34,35].…”
Section: Discussionmentioning
confidence: 99%